Persons with disability negotiating their sexualities - Msekele, Sisanda (My University, 2015)
This ethnographic study looks at how disabled youth in two locations, the University of Witwatersrand and a wheelchair basketball team in Johannesburg, form and negotiate intimate relationships. This is explored by regarding different types of disabilities in order to capture different experiences that different ‘persons with disabilities,’ with different bodies have when it comes to exercising and performing their sexualities. The study finds that the environment that an individual is exposed to plays a contributing role in how one tackles issues of intimacy. Hence, this study explores the role played by exposure by looking into groups of disabled people from different environments: university students and wheelchair basketball players as informants give different kinds of feedback which is highly influenced by the kinds of exposures they face on a daily basis. These two groups of youth help clarify the analysis of different experiences and different disabilities without making generalization about the disabled population in general. This is done in consideration of the South African context where diversity is a rich concept and therefore needs to be acknowledged in understanding how persons with disabilities negotiate their sexualities.
MA Thesis: Anthropology February 2015